2022
DOI: 10.1007/s00432-022-04029-7
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation suppresses DLG2 expression decreasing inflammasome formation

Abstract: Purpose Loss of expression of DLG2 has been identified in a number of cancers to contribute to the disease by resulting in increased tumor cell proliferation and poor survival. In light of the previous evidence that DLG2 alters the cell cycle and affects proliferation, combined with indications that DLG2 is involved in NLRP3 inflammasome axis we speculated that DLG2 has an immune function. So far, there is no data that clearly elucidates this role, and this study was designed to investigate DLG2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…ESR2 (estrogen receptor 2) (rs932657402, p-value=1.13x10 -6 , OR [95% CI]=0.13 [0.06-0.30]) and HGF (hepatocyte growth factor) (rs75427037, p-value=1.57 x 10 -6 , OR [95% CI]=0.23 [0.12-0.42]), have been associated with thrombotic events [31,32], while EPHA7 (rs117489460, p-value=4.50 x 10 -6 , OR [95% CI]=0.19 [0.09-0.38]) is expressed in vascular endothelial cells and shows higher expression levels during inflammation [33]. Other suggestive loci identified in our meta-analysis have been previously associated with other immune-mediated diseases, such as WNT11 (Wnt family member 11) and DLG2 (discs large MAGUK scaffold protein 2) with inflammatory bowel disease, ANKRD50 (ankyrin repeat domain containing 50) with systemic lupus erythematosus, and PLCL1 (phospholipase C like 1) gene expression with rheumatoid arthritis [34][35][36][37].…”
Section: Gwas Results and Meta-analysismentioning
confidence: 62%
“…ESR2 (estrogen receptor 2) (rs932657402, p-value=1.13x10 -6 , OR [95% CI]=0.13 [0.06-0.30]) and HGF (hepatocyte growth factor) (rs75427037, p-value=1.57 x 10 -6 , OR [95% CI]=0.23 [0.12-0.42]), have been associated with thrombotic events [31,32], while EPHA7 (rs117489460, p-value=4.50 x 10 -6 , OR [95% CI]=0.19 [0.09-0.38]) is expressed in vascular endothelial cells and shows higher expression levels during inflammation [33]. Other suggestive loci identified in our meta-analysis have been previously associated with other immune-mediated diseases, such as WNT11 (Wnt family member 11) and DLG2 (discs large MAGUK scaffold protein 2) with inflammatory bowel disease, ANKRD50 (ankyrin repeat domain containing 50) with systemic lupus erythematosus, and PLCL1 (phospholipase C like 1) gene expression with rheumatoid arthritis [34][35][36][37].…”
Section: Gwas Results and Meta-analysismentioning
confidence: 62%
“…Specifically, NFKBIZ has been identified as a novel potential CRC susceptibility gene by exome sequencing of 29 samples from 43 CRC patients that showed familial clustering ( 136 ). The downregulation of NFKBIZ was observed in tumor tissue compared to that in paired healthy mucosa from CRC patients ( 137 ). NFKBIZ mutations are very common in the epithelium of patients with ulcerative colitis but are rarely found in sporadic or colitis-related cancers, suggesting the selection of NFKBIZ-mutant cells during colorectal carcinogenesis ( 138 ).…”
Section: Diseases Related To Iκbζ In the Context Of Inflammationmentioning
confidence: 99%
“…Low levels of NFKBIZ expression in LUAD patients have been associated with reduced overall survival ( 142 ). DLG2 is an important tumor suppressor gene, and DLG2 overexpression leads to an increase in the expression of IκBζ ( 137 ).…”
Section: Diseases Related To Iκbζ In the Context Of Inflammationmentioning
confidence: 99%
“…For example, it is reported that DLG2 is altered in response to inflammation and can activate the formation of NLRP3 inflammasomes. 26 Considering the function of cellular membrane trafficking, STK16 localizes to the Golgi complex and is involved in transporting secretory vesicles, which may indirectly contribute to cytokine production for pro-inflammatory responses. 27 The top-hit gene, BRD2 , is reportedly essential for pro-inflammatory cytokine production in macrophages.…”
Section: Resultsmentioning
confidence: 99%